Techniques for the identification of crosscutting concerns: A systematic literature review - Marçal, Ingrid [UNESP]; Garcia, Rogério Eduardo [UNESP]; Eler, Danilo Medeiros [UNESP]; Junior, Celso Olivete [UNESP]; Correia, Ronaldo C. M. [UNESP] (Springer Nature, 2016)
Modularization is a goal difficult to achieve in software development. Some requirements, named crosscutting concerns, cannot be clearly mapped into isolated source code units, and their implementations tend to cut across multiple units. Although several researches propose new approaches to identify crosscutting concerns, few works aim to provide analysis, synthesis and documentation of the aspect mining literature. To address this research gap, we conducted a systematic literature review to provide researchers with a state-of-the-art of the existing aspect mining techniques. We point out challenges and open issues on most of the techniques analyzed that could be improved in further researches.
Keywords: Aspects; Concerns; Crosscutting-concerns; Crosscuttingness; Review